Conditions and dynamics of magma storage in the Snæfellsnes volcanic zone, western Iceland: insights from the Búðahraun and Berserkjahraun eruptions - Kahl, Maren; Bali, Enikő; Guðmundur H. Guðfinnsson; Neave, David A; Ubide, Teresa; Meer, Quinten H. A. van der; Matthews, Simon (Journal of petrology, 2021)
Establishing the conditions and dynamics of pre-eruptive magma storage and transfer within transient transcrustal storage networks is a major focus of quantitative volcanic petrology. In Iceland, the behaviour, conditions and timescales of magmatic processes within on-rift plumbing systems are increasingly well constrained. However, relatively little is known about magma storage and transfer in off-rift zones, despite off-rift volcanoes being able to generate hazardous explosive eruptions after centuries or millennia of dormancy (e.g. 2010 AD Eyjafjallajökull; 1362 AD Öræfajökull; 3.0 ka, 4.2 ka and 1104 AD Hekla). We present a combined geochemical and geothermobarometric study of magma storage and transfer recorded in the products of the postglacial Búðahraun (∼5.0-8.0 ka) and Berserkjahraun (∼4.0 ka) eruptions within the Snæfellsnes volcanic zone. The eruption products contain diverse and compositionally heterogeneous macrocryst cargoes recording complex petrogenetic histories of crystal evolution and inheritance from different parts of the sub-volcanic plumbing systems. Geothermobarometry indicates two compositionally and thermally heterogeneous magma storage regions located in the lower (20 ± 4 km) and upper-mid (11 ± 3 km) crust. Crystallization pressure and depth estimates coincide with comparable data from Vatnafell, a small sub-glacial table mountain (tuya) in the centre of the Snæfellsnes volcanic zone, indicating that the nature and conditions of magma storage have remained unchanged since the Upper Pleistocene. Trace element zoning of clinopyroxene macrocrysts indicates that mafic recharge into the upper-mid-crustal storage zone triggered the eruptions of Búðahraun and Berserkjahraun. Evidence for eruption-triggering mafic recharge and basaltic cannibalism involving the transfer and amalgamation of crystals with different evolutionary histories sets the Búðahraun and Berserkjahraun eruptions apart from other studied eruptions in Iceland. We propose that the compositional and textural diversity preserved within the crystal cargoes are a direct consequence of the reduced heat flow beneath the Snæfellsnes volcanic zone, which favours the formation of isolated melt pockets in which compositionally diverse macrocryst populations formed. Periodic flushes of primitive basaltic magma from depth promote widespread mixing with evolved melts, resulting in the assembly of crystals with diverse ancestries from different parts of the sub-volcanic systems. Insights gained from the diverse macrocryst cargoes of Búðahraun and Berserkjahraun and comparisons with recent off-rift volcanism in Iceland are essential for the development of future monitoring efforts and hazard evaluation. Although volcanism within the Snæfellsnes volcanic zone differs fundamentally from that in rift zones where eruptions are controlled by extensional spreading, magma ascent from depth still appears to follow pre-existing tectonic escape routes. This could result in extremely short advance warning times on the order of a few days.
Gesehen am 24.12.2021